Alliance formation during disagreement in group discussion among ESL learners - Engku. M. Syafiq; Paramasivam, Shamala; Jalaluddin, Ilyana; Darmi, Ramiza (Secholian Publication, 2022)
The study examines how disagreement is managed by 32 intermediate level Malay ESL students in a Malaysian higher education setting in group discussion in terms of alliance formation. The group discussions in a group of four on a controversial topic were video-recorded to capture how they manage disagreements through the way they formed alliances among themselves throughout the discussion when they expressed opinions using English. The data analysis involved pragmatics as the approach to analyse speech acts and discourse strategies utilised by the participants when they manage disagreements in the discussion. The findings indicate that the participants draw themselves into alliance with one another using various discourse strategies. They managed disagreement in multiple ways using indirect speech acts, and various discourse strategies that are evident in the alliance-making process. The findings could have implications for future studies researching disagreement discourse. Apart from that, implications are also highlighted in terms of pedagogical approaches, and practices, especially in ESL settings. This encompasses the teaching content (e.g.: the importance of pragmatic competence), methodology (e.g.: useful expressions and strategies), and possible activities (e.g.: group discussion) that are effective in assisting teachers to get students to communicate in ESL classrooms.